Anodes for Rechargeable Lithium-Sulfur Batteries - Cao, Ruiguo; Xu, Wu; Lv, Dongping; Xiao, Jie; Zhang, Ji-Guang (Advanced energy materials, 2015)
With the significant progress that has been made toward the development of cathode materials and electrolytes in lithium‐sulfur (Li‐S) batteries in recent years, the stability of the anode in Li‐S batteries has become one of the more urgent challenges in order to reach long‐term stability of Li‐S batteries. In Li‐S batteries, a passivation layer is easily formed on the metallic Li anode surface because of the presence of polysulfides and electrolyte additives. Although the passivation layer on the Li metal anode can significantly suppress Li dendrite growth and improve the safety of Li‐S batteries, continuous corrosion of the Li metal anode eventually leads to battery failure due to the increased cell impedance and the depletion of electrolyte. Here, the recent developments on the protection of the Li metal anode in Li‐S batteries are reviewed. Various strategies used to minimize the corrosion of Li anodes and to reduce its impedance increase are analyzed. Other alternative anodes used in sulfur‐based rechargeable batteries are also discussed. Recent developments on the anodes of lithium‐sulfur batteries are reviewed. Various strategies used to enhance the cycling stability of anodes are analyzed, with a particular focus on how to minimize the corrosion of lithium anodes and suppressing lithium dendrite growth in the presence of polysulfides. Alternative anodes for sulfur‐based rechargeable batteries are also discussed.